2019
DOI: 10.1155/2019/9860381
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Characterization and Its Actions on Immunocompetent Cells of Polysaccharides from Sijunzi Decoction

Abstract: Sijunzi decoction (SJZD) is a classic recipe in Traditional Chinese Medicine (TCM) with strong immune-enhancement activity. To further understand the characterization and immunomodulatory effect of polysaccharides from SJZD, the monosaccharide compositions of crude polysaccharide (SJZDP), polysaccharide fraction (S-3), and homogeneous polysaccharide (S-3-AG) from SJZD were compared by GC analysis, as well as their immunomodulatory effects on Peyer’s patch cells, splenocytes, and macrophages which are related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“… 49 The extraction of different monosaccharide compositions from SJZD has noticeable effects on intestinal immunity, specific immunity, and nonspecific immunity. 50 It has the capability to augment the adaptive immune response, regulate the intestinal immune system, and facilitate the restoration of gastrointestinal function, which is through the reduction of CD3 + T cells and CD8 + T cells, and the elevation of CD4 + T cells. 51 Furthermore, SJZD has demonstrated efficacy in mitigating inflammation by enhancing intestinal local immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 The extraction of different monosaccharide compositions from SJZD has noticeable effects on intestinal immunity, specific immunity, and nonspecific immunity. 50 It has the capability to augment the adaptive immune response, regulate the intestinal immune system, and facilitate the restoration of gastrointestinal function, which is through the reduction of CD3 + T cells and CD8 + T cells, and the elevation of CD4 + T cells. 51 Furthermore, SJZD has demonstrated efficacy in mitigating inflammation by enhancing intestinal local immunity.…”
Section: Discussionmentioning
confidence: 99%
“… 57 Previous studies have consistently shown that SJZD enhanced the diversity and constitution of the gut microbiota, while also exerting an immunomodulatory influence by regulating the gut microbiota. 26 , 50 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that longan polysaccharides can reach the intestine in an undigested form without significant changes in immunomodulatory activity [ 6 ]. Longan polysaccharides may exert immunomodulatory activity by activating macrophages within the intestinal immune system [ 23 ]. The present study showed that polysaccharides extracted from dried and fresh longan differentially promote phagocytosis and NO, TNF-α, and IL-6 secretion.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Crude polysaccharide (SJZDP), polysaccharide fraction (S-3) and homogeneous polysaccharide (S-3-AG) separated from SJZD have immune-enhancing effects, and may have different immune regulation effects on intestinal immunity, specific immunity and non-specific immunity due to their different monosaccharide compositions. 7 Mechanism of action study has shown that SJZD can enhance the immune function of mice by regulating the janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway. 8 SJZD may also help reduce intestinal injury after burns and prevent intestinal bacterial translocation.…”
Section: Introductionmentioning
confidence: 99%